Numerical simulation of bioaerosol particle exposure assessment in office environment from MVAC systems. (June 2018) - Yu, HC; Mui, KW; Wong, LT
Bioaerosol (i.e. biological aerosol) exposures in the office environment are associated with a wide range of health effects. The potential bioaerosol emission from mechanical ventilation and air conditioning (MVAC) systems can endanger the building occupants in office, especially as over 90% of commercial buildings in Hong Kong that are equipped with MVAC systems, due to the microbial growths inside MVAC systems, such as cooling coils and mixing chamber, were reported. This study evaluated the exposure risk of the bioaerosol emission from the MVAC systems to the building occupants. A two-phase flow computational fluid dynamics approach was adopted to simulate the emission, dispersion, deposition, and exhaustion of bioaerosol particles from the MVAC systems in a typical office cubicle by altering the ventilation strategies with four ventilation rates, four emission concentrations, and two microorganism species. The results reported that about 5% contribution of concentration level from the MVAC system including the ventilation rate is sufficient to dilute the biocontainment. This study suggested the importance of the maintenance strategies of MVAC systems for minimizing bioaerosol exposures in offices.